Surface modification of metal oxide films by gold nanoparticles. (September 2019) - Rehacek, V; Hotovy, I; Predanocy, M; Vojs, M; Marton, M
Abstract: The goal of this contribution is to develop a process the most appropriate for the deposition of colloid gold nanoparticles on the surfaces of metal oxides (TiO2, NiO) prepared on silicon and/or alumina substrates. Important procedures such as hydrophilization of metal oxide surface and its subsequent functionalization with a silane coupling agent 3 mercapto propyl tri metoxy silane (MPTMS) were examined so as to reach a metal oxide surface with the most satisfying properties for immobilization of gold nanoparticles having a uniform and dense distribution. TiO2 nanotips prepared by reactive ion etching of oxide surface covered with selfmask gold nanoparticles as well as improved hydrogen gas sensing properties of the NiO film covered by gold nanoparticles are demonstrated.